WOMEN’S IMPACT ON NATIONAL INTEGRATION: CHALLENGES AND PROSPECTS IN KENYA - Laurent, Sophie; Dubois, Pierre (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The concept of national cohesion and integration, as articulated by Kumalo and Sigsworth (2016), encompasses a dynamic process and outcome aimed at instilling in citizens a profound sense of belonging to a unified community engaged in shared endeavors while confronting collective challenges and opportunities. The custodian of this vision is the National Cohesion and Integration Commission (NCIC), a government entity entrusted with the noble mission of nurturing a harmonious national community and advocating peaceful coexistence among the diverse Kenyan populations. Women’s indispensable role in Kenya’s development and national integration cannot be overstated. Despite comprising half of any conflict-ridden or war-affected population, women are often inadequately represented in peace negotiations, as noted by Ellerby (2016). This persistent discrepancy persists despite growing global awareness and policy initiatives regarding the impact of conflict on women and the imperative of their inclusion in peace and security processes. The United Nations’ seminal framework on women, peace, and security underscores the pivotal role women play in conflict prevention and resolution. However, as observed by Walton (2015), women’s active involvement in peace and national integration processes remains marginalized, extending from local to global contexts. This sidelining has far-reaching consequences, as peace agreements and ceasefires frequently fail to address women’s perspectives, needs, and concerns, leading to an absence of post-conflict recovery planning tailored to these requirements. Brounéus (2014) contends that this oversight jeopardizes the long-term sustainability of peace accords. To address this, there is a growing call for increased female participation in peace processes, which has led to the proliferation of women mediator networks, as highlighted by Olofsson (2018). These networks serve to fortify women’s leadership, facilitate coordination, foster collaboration among stakeholders, and share resources and knowledge, ultimately enhancing the capacity of women mediators, as emphasized by Ellerby (2016).